Pediatric Palliative Care - Min Sun Kim (The Korean Society of Pediatric Hematology-Oncology, 2020)
In modern medical environment, death rates of newborn babies, children, and adolescents have decreased while the survival rate of life-threatening diseases has increased drastically. The relative 5 year survival rates of pediatric cancer have increased to over 80% in 21st century, however, the prognosis of certain types of pediatric cancer still remains unfavorable, causing patients and families face physical, psychosocial, and spiritual challenges due to complications as well as intensive treatments such as stem cell transplantation. Pediatric Palliative Care (PPC) is a specific system with a philosophy of care to respond to psychosocial and spiritual needs of patients and families as well as control pain and symptoms offered in order to satisfy unique and special needs of children and adolescents living with life-threatening disease, to ensure health-related human rights of children and adolescents. Essential elements of PPC, communication with the child or adolescent patient and family, pain and symptom control and care for the time of death and bereavement have been described.